The prognosis following amphetamine poisoning. Issue 8 (December 2017) - Horwitz, Henrik; Dalhoff, Kim P.; Klemp, Marc; Horwitz, Anna; Andersen, Jon T.; Jürgens, Gesche
Aims: This study investigated the long-term mortality following poisoning by amphetamine or substituted amphetamines. Furthermore, we examined the social problems and somatic and psychiatric co-morbidity related to amphetamine poisoning, and their impact on the long-term survival. Methods: We identified amphetamine poisoned patients from the Danish Poison Information Centre database and correlated their personal identification numbers with seven Danish national registries related to different social and health aspects. For each case, we sampled 100 age and gender matched controls from the background population. Results: From August 2006 to December 2013 we identified 1444 patients (70% males) who experienced amphetamine poisoning; 52% of the cases were classified as mixed poisonings and the average age at first contact was 24.8 years (SD 8.6). The prevalence of psychiatric disorders, HIV, viral hepatitis, and previous prison incarceration was approximately 10 times higher than among healthy controls. After seven years 11% were deceased as opposed to 0.6% in the control group, and 64% of the patients died from unnatural causes. Male gender (HR 2.29, 95% CI (1.07-4.90)), age (HR 1.06, 95% CI (1.03-1.09)), opioid dependence (HR 2.88, 95% CI (1.42-5.85)), schizophrenia (HR 3.09, 95% CI (1.63-5.86)), affective disorders (HR 2.65, 95% CI (1.44-4.90)) and HIV (HR 5.45, 95% CI (1.19-24.90)) were associated with a high mortality. Furthermore, a significant proportion of these patients experienced social and health related deterioration in the years following poisoning. Conclusions: Amphetamine poisoning is associated with a poor long-term prognosis and is complicated by additional social and health related issues .